A rare case of bilateral cavitary inferior olive lesions in brain autopsy of an adult patient - Mireille Bitar, M.D.; Francisco Zaldana, M.D. (Human Pathology: Case Reports, 2018)
Bilateral lesions of the inferior olivary nucleus are extremely rare. We report a rare case of bilateral inferior olivary cavitary lesions detected at autopsy. We hereby discuss the plausible disease entities that may cause this pathological presentation.